Faktor-Faktor Yang Berhubungan Dengan Keluhan Computer Vision Syndrome (CVS) Pada Pekerja Divisi Teknologi di PT INKA (Persero) Madiun - Syifa Farida Ashaar; Tyas Lilia Wardani; Farhana Syahrotun Nisa S (Sekolah Vokasi, Universitas Sebelas Maret, 2022)
The technology division at PT INKA (Persero) is a division responsible for carrying out work related to industrial technology and requires workers to use two computer monitors for 8 working hours. This can lead to workers being more vulnerable to experiencing CVS. This study is an analytical observational study with a cross sectional approach. The respondents of this study were all 55 technology division workers at PT INKA (Persero) with sampling techniques using total sampling. The data analysis techniques used are Somers'd for bivariate tests and logistic regression for multivariate tests. The results of the Somers'd correlation showed that from the 4 factors analyzed there were 2 factors that were significantly related to CVS complaints, namely the use of a blue light filter (p = 0.018) and the length of eye rest (p = 0.00). Based on the results of the logistic regression test, it is known that the most related factors related to CVS complaintsis the length of eye rest time (OR = 33.181).